GAMBARAN PROSES IMPLEMENTASI REKAM MEDIS ELEKTRONIK DI UNIT RAWAT JALAN DENGAN METODE HOT-FIT DI RUMAH SAKIT UMUM ARI CANTI - Ni Ketut Juliantari; Luh Yulia Adiningsih; Putu Chrisdayanti Suada Putri; Gede Wirabuana Putra; Putu Erma Pradnyani (MAINTEKKES : The Journal of Management Information and Health Technology, 2023)
Electronic medical records are very important to overcome various problems that often occur in hospitals such as the loss of medical records, large storage areas, and PERMENKES Republik Indonesia Number 24 of 2022 concerning Medical Records, Article 45 states that all health service facilities hold electronic medical records in accordance with the provisions in this ministerial regulation no later than December 31, 2023. At Ari Canti General Hospital there are no complaints related to services, but Ari Canti General Hospital is still semi-medical records. An electronic medical record is a version of a paper medical record that is made electronic. Barriers to the implementation of electronic medical records in hospitals include 4 aspects including human resources (HR), policies and regulations, infrastructure and costs, This study aims to describe the process of implementing electronic medical records with the Hot-Fit model. This model places important components in information systems, namely Human, Organization and Technology and Net-benefit. The result of this study is that there is a significant relationship between human, organizational, and technological components to net-benefit.